2015
DOI: 10.3899/jrheum.150565
|View full text |Cite
|
Sign up to set email alerts
|

Is Disease Activity in Rheumatoid Arthritis during Pregnancy and after Delivery Predictive for Disease Activity in a Subsequent Pregnancy?

Abstract: RA disease course in following pregnancies cannot be predicted based upon previous pregnancies. However, a flare postpartum seems to predict subsequent flares.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…However, this factor would not help us in the daily practice, since we do not have the genetic profile of every patient and her offspring. Additionally, research has recently shown that the disease course in a first pregnancy is not predictive for a subsequent pregnancy (21). We considered the sex of the child as an influential factor, but this factor also did not reach statistical significance (data not shown).…”
Section: Discussionmentioning
confidence: 96%
“…However, this factor would not help us in the daily practice, since we do not have the genetic profile of every patient and her offspring. Additionally, research has recently shown that the disease course in a first pregnancy is not predictive for a subsequent pregnancy (21). We considered the sex of the child as an influential factor, but this factor also did not reach statistical significance (data not shown).…”
Section: Discussionmentioning
confidence: 96%
“…The inclusion of a second or subsequent pregnancy might introduce bias, since it may represent a selection bias for women who previously had a good experience with their RA course during and after pregnancy and/or a good experience with the outcome of the pregnancy. On the other hand, it has been demonstrated that RA disease course in subsequent pregnancies cannot be predicted based upon previous pregnancies ( Ince-Askan et al, 2016 ). We included pregnancies from 2000 to 2018, a long period in which the management of RA during pregnancy has been changing.…”
Section: Discussionmentioning
confidence: 99%
“…This study is embedded in the Pregnancy-induced Amelioration of Rheumatoid Arthritis (PARA) study, a prospective cohort study on pregnancy and RA 29. From 2002 to 2008, 369 female patients with RA who had a wish to conceive (or already pregnant) were enrolled 30 31. After participation in the PARA study, 196 children and their parents were invited to participate in a follow-up study, the FEtal Programming in Rheumatoid Arthritis (FEPRA) study.…”
Section: Methodsmentioning
confidence: 99%